Boundary behavior for the large viscosity solutions to equations involving the infinity-Laplacian. Issue 12 (10th September 2017) - Chen, Yujuan
Abstract : The paper shows the new boundary behavior of large viscosity solutions to the infinity Laplacian equations, where f ( u ) is a function whose variation at infinity may be regular or rapid, b may be degenerate or singular at the boundary